The Role Of Product Innovation, Competitive Advantage, And Marketing Plan In Improving Marketing Performance - Atmanegara, Stivaniyanti; Swastika, Melur Tri; Mawazin, Khusnul; Carissa, Maisie Alma (Majalah Ilmiah DIAN ILMU, 2024)
Product innovation, competitive advantage and marketing strategy are one of the indicators to measure the success and success of managing a business. Because product innovation and product excellence are variables that are believed to be able to improve marketing performance, especially for micro, small and medium enterprises (MSMEs). The type of research method used in this study is quantitative method. The research design was with a primer derived from a closed questionnaire. The method of collecting questionnaire data is by purposive sampling technique. The data collected in this study used questionnaires. The purpose of this study is to directly examine the variables of product innovation, competitive advantage and marketing strategy on marketing performance. To consumers. The number of samples included in this study was 82 and PLS3 was used as an analysis tool. The results showed that the influence of product innovation, competitive advantage, and marketing strategy has a positive effect on marketing performance.